The Effect of Using Picture Media Towards Students’ Vocabulary Mastery at The Eighth Grade Students of Islamic Junior High School Students of Mathla’ul Anwar Dahu Bojong in Academic Year 2018/2019 - Wahyu Wiganda Putra (Universitas Mathla'ul Anwar Banten, 2020)
The purpose of this study is to investigate the effect of using picture media towards students’ vocabulary mastery at the eighth grade students of MTs Mathla’ul Anwar Dahu Bojong which was located on Jl. Prapatan Warungkupa Km. 01 Kp Dahu. Ds. Mekarsari Kec. Bojong Kab. Pandeglang, 42273. The population of this study was 50 students and the sample was 50 students. This study is carried out to find out whether there is a significant effect of using picture media towards students’ vocabulary mastery. This research used a quantitative true experimental approach using Pretest-Posttest Control Group Design. In this research there are two variables, they are independent variable and dependent variable. The independent variable is Picture media (X), and then the dependent variable is Vocabulary Mastery (Y). In collecting the data this research used multiple choice test as instrument.The hypothesis analysis used analysis of t-test. In analysing the hypothesis this research used SPSS statistics 22. Finding of this study showed that there is a significant effect of using picture media towards students’ vocabulary mastery. It could be seen that t-count= 3.503 and signification value (p-value) = 0.001 < α = 0.05, so H1 is accepted and H0 is rejected. On the other word, there is a significant effect of using picture media towards students’ vocabulary mastery. Based on the result above, the researcher concluded that vocabulary is one of the elements in English. Teaching English using Picture Media gave positive contribution especially on improving vocabulary mastery.